Principales complicaciones posquirúrgicas asociadas a las exodoncias de terceros molares mandibulares. - Revelo Martínez, Belén Estefania (2023)
Currently the extraction of mandibular third molars is one of the most developed procedures in dentistry, especially in the field of Oral Surgery. The purpose of this research work is to determine the main post-surgical complications associated with mandibular third molar extractions, by means of a bibliographic review of the scientific literature, which was achieved through the search of various scientific articles, books, case studies and meta analysis, indexed in databases such as PubMed, Elsevier, Science Direct, Scielo and Google Scholar in a time frame of the last 10 years. The results show that after the extraction of mandibular third molars, complications associated with the procedure may occur. The most frequent complications found in the literature are hemorrhage, hematoma, edema, trismus and pain (immediate complications), while alveolitis and uncommon conditions such as infections and nervous accidents (mediate or later complications), this classification highlights pain, inflammation and trismus as characteristic and transitory complications after the extraction process, however they tend to become real discomforts for patients. At the same time, it is considered that the appearance of the mentioned complications can be implicated by diverse factors such as the systemic condition of the patient, type of surgery and surgical trauma, experience of the surgeon, postoperative care, and in certain complications attributable to the gender factor. Therefore, it was concluded that before this type of procedures, an adequate preoperative planning should be done with all the knowledge and auxiliary methods in dentistry such as radiographies, tomography’s or laboratory tests, thus guaranteeing an optimal recovery and a successful treatment for our patients.